2009
DOI: 10.1002/jsfa.3560
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and non‐volatile acids of noni (Morinda citrifolia L.) fruit

Abstract: BACKGROUND: Volatile and non-volatile acids were analysed in noni (Morinda citrifolia L.) fruit by a combination of conventional sampling methods with gas chromatography/flame ionisation detection and gas chromatography/mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…Minerals account for 10-12% of the dry matter , mainly potassium, sulphur, calcium and phosphorus and amino acids, such as aspartic acid. It also contains caproic and caprylic organic acids, but the malic acid is the predominant one (Pino et al, 2008). However, the observed beneficial health effects may be the result of certain compounds that differ from those present in other common fruits, such as phenols (damnacanthal and scopoletin), nitric oxide, alkaloids and sterols and also could be due to the antioxidant potential of noni.…”
Section: Introductionmentioning
confidence: 94%
“…Minerals account for 10-12% of the dry matter , mainly potassium, sulphur, calcium and phosphorus and amino acids, such as aspartic acid. It also contains caproic and caprylic organic acids, but the malic acid is the predominant one (Pino et al, 2008). However, the observed beneficial health effects may be the result of certain compounds that differ from those present in other common fruits, such as phenols (damnacanthal and scopoletin), nitric oxide, alkaloids and sterols and also could be due to the antioxidant potential of noni.…”
Section: Introductionmentioning
confidence: 94%
“…These compounds included organic acids (mainly octanoic and hexanoic acids), alcohols (3-methyl-3-buten-1-ol), esters (methyl octanoate, methyl decanoate), ketones, (2-heptanone), and lactones [(E)-6-dodeceno-␥ -lactone]. Pino et al (2009) reported 34 volatile compounds in noni fruit harvested at the soft white stage of maturity using conventional extraction procedures and the gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectroscopy (GC-MS) analysis. The main volatile acids identified were, octanoic acid (3.06 g/kg) followed by hexanoic acid (0.33 g/kg).…”
Section: Chemical Composition and Flavormentioning
confidence: 99%
“…Its pulp is juicy and bitter, light dull yellowish white, gelatinous when the fruit is ripped. Octanoic acid and hexanoic acid are the major volatile acids, while malic acid, malonic acid and fumaric acid are the main non-volatile acids [3]. The major phytochemical components in noni (Morinda citrifolia L.) are phenolic acid, organic acid, glycosides, polysaccharides, iridoids, alkaloids, lignans, trisaccharide fatty acid esters, anthraquinones, scopoletin, morindin, vitamins, minerals and alkaloids [4,5,6].…”
Section: Introductionmentioning
confidence: 99%